Efektifitas Kelengkapan Pendokumentasian Buku KIA untuk Deteksi Resiko Tinggi Kehamilan - Pedvin Ratna Meikawati; Ana Setyowati; Ni’matul Ulya (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2020)
The Maternal and Child Health Book (KIA) is a form of family and community active participation in the field of maternal and child health. The successful application of the MCH Handbook as a tool to increase the coverage of MCH services is inseparable from the role of the parties related to the health of pregnant women, mothers in labor, newborns, infants and toddlers. The MCH Handbook has several uses, among others, as a guide for mothers and children to contain information and records on maternal and child health, and the MCH handbook serves as the only means of recording maternal and child health. This study aims to analyze the completeness of documenting pregnant women data from the MCH Handbook at the Pekalongan City Health Center. This research was conducted using a combination of quantitative and qualitative research methods (mixed methodology). Quantitative research uses survey research methods and a cross sectional approach, where the variables are measured at the same time. The population in this study was the KIA book, while the samples in this study were midwives who were serving at the Puskesmas with a minimum work period of 1 year and pregnant women who were having their pregnancies examined, the sample size was determined by the incidental sampling method and purposive sampling based on the health center used. The test results with logistic regression obtained p value <0.05 and the value of Exp (B) ≥ 2 is the variable of tenure. The working period variable has a p value of 0.095, the value of Exp (B) is 10.0 (OR ≥ 2), while the history variable does not have a p value <0.05, namely with a p value of 0.341, the value of Exp (B) is 3.0. So it can be concluded that there is no effect of working period and history together on the completeness of the MCH book documentation for early detection of high risk in pregnancy. Midwives at the Pekalongan City Health Center are advised to further improve the completeness of the MCH Handbook in the early detection of high-risk pregnant women. Increase motivation to midwives by rewarding midwives who have performed their duties well.